The Sibling Relationship in Foster Care: Policy Implications - Kate Sheehan (Columbia Social Work Review, 2017)
The majority of children placed into foster care are separated from their siblings upon entering the child welfare system. Some research suggests that siblings enjoy more stable home environments and fewer behavioral problems when placed together in care. The sibling relationship may provide stability, consistency, and unconditional positive regard to the children most at risk for poor outcomes such as anxiety, depression, low self-esteem, and loss of identity. This paper argues that foster care and child welfare agencies must institute the changes necessary to make sibling relationships a priority. Recommendations for integrating the protection of sibling relationships in the placement process are proposed.